Leadership Behavior and Employee Voice: Is the Door Really Open? - Detert, James R.; Burris, Ethan R. (Academy of Management Journal, 2007)
We investigate the relationships between two types of change-oriented leadership (transformational leadership and managerial openness) and subordinate improvement-oriented voice in a two-phase study. Findings from 3,149 employees and 223 managers in a restaurant chain indicate that openness is more consistently related to voice, given controls for numerous individual differences in subordinates' personality, satisfaction, and job demography. This relationship is shown to be mediated by subordinate perceptions of psychological safety, illustrating the importance of leaders in subordinate assessments of the risks of speaking up. Also, leadership behaviors have the strongest impact on the voice behavior of the best-performing employees.